Improving the Ability to Write Cursive Letters Using Picture Cards in Elementary School Students - Antonius Tonny Budisantoso; Siti Rochmiyati (Universitas Pendidikan Ganesha, 2026)
The low ability to write cursive letters among grade IV elementary school students remains a problem in learning to write. This condition is indicated by the inaccuracy of letter forms, neatness, and inconsistency of writing according to applicable rules. This study aims to analyze and evaluate the effectiveness of picture cards in improving grade IV students' cursive letter writing skills. The study used a classroom action research (CAR) approach, implemented in two cycles, each consisting of two meetings. Data were collected through cursive writing performance tests, observation of student activities, and documentation with an instrument in the form of a writing skills assessment rubric. Data analysis techniques were carried out descriptively, quantitatively, and qualitatively by comparing the percentage of learning outcomes completion in each cycle. The results showed a gradual increase in students' ability to write cursive letters, from 20% in cycle I meeting I to 75% in cycle II meeting II. The conclusion of this study shows that the use of picture cards is effective in improving grade IV students' ability to write cursive letters. This research aims to strengthen the role of visual media in learning writing skills and to provide an effective, easy-to-use alternative learning medium for elementary school teachers.